REPRESENTASI WANITA PADA IKLAN TELEVISI WARDAH COSMETIC (Analisis Semiotik Roland Barthes Wardah Inspiring Beauty Versi True) - Ilona Oisina Situmeang (Universitas Bunda Mulia, 2015)
This study aims to determine the signifier and signified which represents about women in television commercials Wardah Cosmetic Beauty Inspiring True Colours version. This study uses a constructivist paradigm, qualitative research with semiotic approach method using Roland Barthes' semiotic theory. Researchers chose Wardah Cosmetic ads as the research object. Wardah ads Inspiring Beauty True Colors version shows that all Indonesian women can give a beautiful inspiration for their surroundings. Based on the research, it can be concluded that the multilevel meaning of Barthes' semiotic theory is through denotative, connotative and myths. Denotation of the Wardah ads True Colors version illustrates that all women who use Wardah cosmetic can give inspiration to others started with always giving a smile. Connotation on the ad depicts that all women were able to inspire the meaning of beauty to others. Myth on this ads is a beautiful woman is usually associated with women who have long hair, white skin, sharp nose, as well as having the ideal body. Keywords: Representation of women, Semiotic, TV Advertisement.